Middle management's role in post-acquisition cultural integration - Kannisto, Johanna (My University, 2019)
Post-acquisition cultural integration is a challenge for many companies and incompatibility of merged cultures is still one of the main reasons if M&As are unsuccessful and the desired synergies are not accomplished. Post-acquisition cultural integration can be a challenging phase that requires careful management, and the role of middle management in this cultural fit cannot be dismissed. The purpose of this study is to examine middle management’s role in post-acquisition cultural integration. The research question “What is middle management’s role in post-acquisition cultural integration?” is analysed in light of sensemaking theory. The research question is divided into three sub-questions: (1) “How do individuals make sense of post-acquisition cultural integration?” (2) “What roles and sense are given to middle managers in post-acquisition cultural integration?” and (3) “How middle managers are able to influence through sensegiving to cultural integration?”. The relationship between organisation culture and M&As, the relationship between post-acquisition integration and cultural fit, and the relationship between middle management and post-acquisition cultural integration are studied in the literature overview. A theoretical framework is based on a sensemaking theory, which guides the empirical study. The qualitative research was conducted through six semi-structured, in-depth retrospective interviews with respondents from top to middle managers in various organisations. The research data in this study was analysed based on the Gioia methodology, which emphasises the respondent’s own language, minimising the need for interpretation. Based on the analysis, middle manager’s role in post-acquisition cultural integration can be seen as a messenger, a broker and an implementer. From sensemaking perspective middle managers understand, interpret and create sense of changing organisational environment. They seek to understand the objectives of M&A as they receive cues from top management. Middle managers are in the intersection of cultures where they try to understand both cultures and simultaneously introduce new culture. From sensegiving perspective middle managers influence the interpretations of the team members by promoting discursive activities and telling stories. This interaction between middle manager’s sensemaking and sensegiving gives a direction to cultural integration in post-acquisition phase of M&A.
Keywords: Organisation culture, cultural integration, middle manager, sensemaking, sensegiving